Analysis of teacher instructional communication barriers - Yumelda Sari (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2022)
During the Covid-19 pandemic, education in Indonesia was held using the blended learning method, or a combination of online and offline education and learning patterns. This condition creates obstacles for teachers in the Districts of Kebon Jeruk and Grogol Petamburan in the process of effective learning communication. This study aims to identify barriers to teacher instructional communication in two sub-districts during the Covid19 pandemic. Empirically this research was conducted so that pedagogic competence in terms of teacher instructional communication can create a climate of Active, Innovative, Creative, Effective, and Fun Learning (PAIKEM). The discussion in this study uses the Shannon Weaver communication model. This study uses qualitative and descriptive methods with a case study approach. Data collection was also carried out by observing the teachers of SDN Duri Kepa 03 Kebon Jeruk District and Al Chasanah Junior High School, Grogol Petamburan District, West Jakarta while teaching offline and online. This study uses purposive sampling, ie from the beginning, the sample has been determined with specific considerations, namely those who are considered to have the ability and competence to provide maximum data. The results showed that the steps in instructional communication could overcome the communication barriers. The conclusion of this study is that by identifying communication disorders that occur and carrying out 10 steps of instructional communication, then pedagogic competence in terms of aspects of teacher instructional communication during the Covid-19 pandemic can be overcome.